Internet addiction among adolescents: prevalence, risk factors and impact on mental health - Bansal, Anuradha; Pawandeep, F. N. U.; Basu, Srikanta; Ranjan, Tulika; Dubey, Himanshu; Saran, Tania (International Journal of Contemporary Pediatrics, 2026)
Background: Internet addiction (IA) is defined as compulsive use of internet resulting in significant impairment to the user. We conducted this study to understand the prevalence of IA and its impact on mental health of adolescents. Methods: In this prospective cross-sectional study, school and college going students of age group 14-19 years were enrolled. They administered a pre-structured questionnaire to assess the pattern of internet use, level of IA and impact of internet on their mental health. Results: Overall, 445 eligible students were enrolled in the study. Majority participants were in the age group of 16-17 years (83.2%). The prevalence of moderate to severe IA was 23.8%. Internet use for more than 4.5 hours a day and use of social media platforms were significant risk factors for development of IA. There was a significant correlation between IA and stress, depression or anxiety Conclusions: About one-fourth of adolescents have IA. There is a need to reduce the use of social media and limit the duration of internet use to prevent the development of addiction.